Distribution and association between environmental and clinical isolates of Cryptococcus neoformans in Bogotá-Colombia, 2012-2015 - Norida Vélez; Patricia Escandón (Memorias do Instituto Oswaldo Cruz)
The propagules of the fungal species Cryptococcus neoformans and C. gattii, whose varieties are distributed world wide, are the primary cause of cryptococcosis, a life threatening disease. The study of environmental and clinical isolates of Cryptococcosis is an important contribution to the epidemiology and ecology of the fungus. The aim of this work was to determine the presence of C. neoformans and C. gattii in the environment in Bogotá, Colombia’s capital city and to establish the relation between clinical and environmental isolates in the period 2012-2015. From a total of 4.116 environmental samples collected between October 2012 - March 2014, 35 were positive for C. neoformans var. grubii. From 55 cryptococcosis cases reported in Bogotá during 2012-2015, 49 isolates were recovered. From those, 94% were identified as C. neoformans var. grubii molecular type VNI; 4% as VNII and 1,2% as C. neoformans var neoformans VNIV. The 84 detected clinical and environmental isolates studied had a similarity between 49-100% according with molecular typing. The correlation between environmental and clinical samples confirms the hypothesis that patients acquire the disease from environmental exposure to the fungal propagules.